POLA PENGASUHAN YANG BERDASAR BUDAYA, AGAMA DAN NEUROSAINS - Mahastuti, Dewi (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Children is a tremendous boon and a mandate that has been entrusted by God to parents, to be educated and cared for as well as possible so that it becomes an individual with strong character in his religion, ethics, thought patterns and sosioemosionalnya. The childcare is how parents guiding and educating children daily (Hurlock, 1998). Parenting will shape the character of the child. Children is a good observer or observers, so what it does is a representation of the daily parental education. Have we thought that the negative program which (may) we inadvertently instilled into the subconscious mind of our children, will continue to dominate and control her life - making a mess in the future ?. To answer these problems then nurturing it is filled with charges are quite dense, in accordance with the ultimate goal of what you want to achieve a parent for his son's future. Parenting charged local culture and customs ethics eastern instill character values for children who have unggah ungguh, manners and ethics. Parenting can not escape from the influence of local culture, upbringing certainly be colored by the local customs and cultural values. Religion in this case Islam became the basic guidelines for parents to take children into a personal smart grateful and in accordance with the command of Allah. How can parents educate children to enter a value and must be in accordance with the thinking pattern of the child, so the child can receive the information properly. The child can receive and process the brain well, so that what has been learned and understood the child will settle into a foundation in his behavior in the future.